Price competition in pharmaceuticals: does tendering significantly reduce medicines prices in the Ministry of Health Malaysia? / Farahwahida Mohd Kasim - Mohd Kasim, Farahwahida (2015)
The increasing trends on drugs expenditure in Ministry of Health Malaysia (MOH) and not fully understands the strategic approach for cost containment is becoming a growing concern for financial sustainability. Although price competition through tendering is one of the substantial methods used to reduce medicine prices but not much is known about the pharmaceutical competitiveness and factors that affects the market price in Malaysian tendering system. Thus, the trends on the pharmaceutical pricing in a highly competitive environment need to be explored. This research aims to study the price effect of actual competition between innovator medicines and then comparators through an open tender system in the MOH public procurement setting. It specifically studies the price difference between the bidders of innovator medicines, the magnitude of price markdown between innovator and their generic comparators, the savings made from generic competition and the factors that contributes to price markdown in an actual drug competition in the MOH. Overall, this study suggests that competition between innovator and generic medicines in tender competition is worth it for MOH savings. The results of the study also suggested that competition between bidders of innovator medicines is only competitive with the entry of generic competitors in MOH tendering system. The price offered by innovators and local generics were found to be less competitive compared to imported generics. The participation of imported generic in the tender competition would be the main determinants that could offer cheaper medicines in the MOH procurement setting.